Friction stir welding : dissimilar aluminium alloys - Siddiquee, Arshad Noor; Khan, Noor Zaman; Khan, Zahid Akhtar (CRC Press, 2017)
"The evolution of mechanical properties and its characterization is important to the weld quality whose further analysis requires mechanical property and microstructure correlation. Present book addresses the basic understanding of the Friction Stir Welding (FSW) process that includes effect of various process parameters on the quality of welded joints. It discusses about various problems related to the welding of dissimilar aluminium alloys including influence of FSW process parameters on the microstructure and mechanical properties of such alloys. As a case study, effect of important process parameters on joint quality of dissimilar aluminium alloys is included."--Provided by publisher